Case report: Intravitreal methotrexate in intraocular acute lymphoblastic leukemia - Pederzolli, Matteo; Giglio, Fabio; Cicinelli, Maria Vittoria; Marchese, Alessandro; Modorati, Giulio; Mastaglio, Sara; Ciceri, Fabio; Bandello, Francesco; Miserocchi, Elisabetta (Frontiers in Oncology, 2022)
Direct leukemic infiltration of the eye is most frequently associated with acute lymphoblastic leukemia (ALL), probably due to its well-known central nervous system (CNS) tropism. Systemic treatment alone may not be sufficient for intraocular leukemia. Data on local treatment is scarce. Here, we present two cases of intraocular ALL treated with intravitreal methotrexate (MTX). Initially, anatomical improvement and visual stability were observed. The first patient experienced anatomical and visual worsening after a year of treatment. Treatment was withheld after two months for the second patient due to poor systemic conditions. Corneal toxicity and intraocular pressure elevation were observed in the first case. In both cases, eye involvement was associated with CNS or systemic relapse. This highlights the importance of incorporating ocular disease management in a comprehensive approach to therapy. Our experience corroborates previous findings on MTX injections as an effective and safe therapeutic option for intraocular leukemia. Further evidence is needed to consolidate the use of intravitreal MTX to treat such a debilitating localization of leukemia.